Covers classification in multi spectral satellite images by means of cellular automata with precision agriculture concepts - Jiménez-López, Andrés Fernando (Universidad Pedagógica y Tecnológica de Colombia - UPTC, 2007)
To carry out the classification process and the generation of thematic maps of earthly cover in multispectral and hyperspectral satellital images different procedures are utilized such as: the spectral analysis, the angular classification, the image dimension reduction and the spectral mixtures linear analysis. In this paper a LandSat 7 Satellital image is employed for realizing the covers classification by means of cellular automata, using each image pixel as a grid element which composes the cellular automata and the results are compared with the obtained ones using the ERDAS Software.